2020
DOI: 10.3390/ijerph17217730
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Importance of Climatic Factors in COVID-19 Worldwide Intensity

Abstract: The transmission of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the severity of the related disease (COVID-19) are influenced by a large number of factors. This study aimed to investigate the correlation of COVID-19 case and death rates with possible causal climatological and sociodemographic factors for the March to May 2020 (first wave) period in a worldwide scale by statistically processing data for over one hundred countries. The weather parameters considered herein were air temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 64 publications
3
37
0
Order By: Relevance
“…[13]. In general, several studies present the hypothesis that atmospheric pollution associated with certain climatological factors (such as, high humidity and low wind speed) may support a longer permanence of viral particles in the air, fostering the rapid spread of COVID-19 within polluted regions [5,11,12,14,15]. In this context, Martorell-Marugán et al [16] suggest new tools for supporting increased data analysis and statistical capabilities that allow users to explore trends and associations between critical environmental data and the spread of COVID-19 in society.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…[13]. In general, several studies present the hypothesis that atmospheric pollution associated with certain climatological factors (such as, high humidity and low wind speed) may support a longer permanence of viral particles in the air, fostering the rapid spread of COVID-19 within polluted regions [5,11,12,14,15]. In this context, Martorell-Marugán et al [16] suggest new tools for supporting increased data analysis and statistical capabilities that allow users to explore trends and associations between critical environmental data and the spread of COVID-19 in society.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…Other ecological studies have evaluated the relationship between environmental factors and SARS-CoV-2 infection, and many have found an inverse relationship between air temperature and humidity and SARS-CoV-2 infection [2,12,13,[18][19][20][21][22]. These studies have been based on COVID-19 reported cases that may be affected by differences in the completeness of reporting.…”
Section: Discussionmentioning
confidence: 99%
“…The Geographical Institute was consulted to obtain the province extension, as well as the latitude and altitude above sea level of their respective capital city (https://www.ign.es/web/ign/portal/ane-datos-geograficos/-/datos-geograficos/ datosPoblacion?tipoBusqueda=capitales, accessed date 21 January 2021). Population density was calculated as inhabitants per km 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations